KUAT TEKAN BETON DENGAN SUBSTITUSI PARSIAL SISA BUBUT BESI SEBAGAI AGREGAT HALUS - Anggara Yunanda; Rafki Imani; Rita Nasmirayanti (Politeknik Negeri Jakarta, 2022)
One of the concrete technologies developed to obtain good compressive strength of concrete is additional material for iron lathe waste obtained from the residue of the iron turning process. This study aims to determine the effect of iron lathe waste as a fine aggregate additive on the compressive strength of concrete. The compressive strength test of concrete was carried out based on The SNI standard 1974:2011. The sample making of the specimens was carried out by varying 0%, 1.5% and 2.5% of iron lathe waste from the weight of fine aggregate in a concrete mixture with a concrete compressive strength of 29.05 MPa. Concrete samples were tested at the age of 7 days, 14 days, and 21 days. The test results show that the maximum compressive strength of concrete is achieved by normal concrete (0%) which is 28.96 MPa at the age of 21 days of concrete. While the value of the compressive strength of concrete after being given a mixture of iron lathe waste decreased. The optimum concrete compressive strength with the addition of iron lathe waste was obtained at 24.63 MPa with a mixture of 1.5% at the age of 21 days of concrete. The decrease in the compressive strength of concrete due to the addition of iron lathe waste. It occurs because of the air trapped in the concrete, causing the concrete to be hollow and not solid, so that the compressive strength of the concrete decreases. Keywords: Fine aggregate, Strength of concrete, Waste iron, Concrete technology.